2000
DOI: 10.1080/07315724.2000.10718079
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Controlled Study on the Effects of Dietary Diacylglycerol on Postprandial Serum and Chylomicron Triacylglycerol Responses in Healthy Humans

Abstract: In the usual range of fat intake (10-44 g), postprandial response after ingestion of DG emulsion was significantly less than that after ingestion of TG emulsion in healthy human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(125 citation statements)
references
References 40 publications
5
118
0
Order By: Relevance
“…2. As reported in previous studies in rodents and humans (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), in the present study, there was a significant reduction in the postprandial total serum TG level after DAG administration compared with that after TAG administration (Fig. 2, top panel, p ϭ 0.028 (time ϫ oil) by repeated measures two-way ANOVA, p Ͻ 0.05 at the 1 and 2-h time-points by Student's t test).…”
Section: Changes In Postprandial Total Serum Tg and Cholesterol Levelssupporting
confidence: 70%
“…2. As reported in previous studies in rodents and humans (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), in the present study, there was a significant reduction in the postprandial total serum TG level after DAG administration compared with that after TAG administration (Fig. 2, top panel, p ϭ 0.028 (time ϫ oil) by repeated measures two-way ANOVA, p Ͻ 0.05 at the 1 and 2-h time-points by Student's t test).…”
Section: Changes In Postprandial Total Serum Tg and Cholesterol Levelssupporting
confidence: 70%
“…Recent studies have suggested that DG consumed in larger amounts may have metabolic characteristics distinct from TG, which may produce bene®cial effects with regard to prevention and management of obesity. Experimental studies in animals and humans have shown that DG reduces postprandial triglyceridemia compared with TG control (Murata et al, 1994;Taguchi et al, 2000). In controlled feeding studies, DG reduced body weight and abdominal fat stores in Japanese men .…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not detect obvious additive or synergistic significances. The physiological functions of DAG appear to be defined by dietary conditions, as indicated by Taguchi et al 12) In our study, the expected physiological effects of the combined DAG and SPI diets were small in the lipid profiles of the rats. Therefore, it might be necessary to take dietary conditions into consideration in order to achive beneficial functions of food components.…”
Section: Discussionmentioning
confidence: 67%
“…12,14,24) Since the physiological benefits and the mechanisms of SPI and DAG have been established, 11,28) the physiological impacts of simultaneous intake of foods and food components of similar function are expected Values are means AE SEM for five rats. When there was a significant interaction between dietary oil and protein, the significance of differences among groups was analyzed by Fisher's PLSD test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation